2011
DOI: 10.1080/15528030.2011.592121
|View full text |Cite
|
Sign up to set email alerts
|

Transcending the Negative: Spiritual Struggles and Resilience in Older Female Trauma Survivors

Abstract: Qualitative data were gathered during a spiritually focused intervention with older women. Participants (n = 36) had experienced some combination of childhood sexual or physical abuse, emotional abuse, domestic violence, and/or sexual assault over their life span. The women described an array of positive spiritual coping strategies, including their persistent action to find God by transcending negative or "man-made" images of God given to them by their religious traditions. They reported persistence in their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“… 35 Protective factors against the development of PTSD in rape and sexual assault survivors include positive social support, 22 , 36 38 strong religious beliefs, 39 positive coping styles, 38 , 40 , 41 self-efficacy, 41 , 42 parental affection, 18 high internal locus of control, 41 and the finding of meaning in the experience. 37 , 39 Various studies have found a link between unresolved attachment (in adults), disorganized/insecure attachment (in infants), and increased likelihood of traumatic dissociation and PTSD symptom severity. 43 48 Insecure attachment is related to social withdrawal and a lack of confidence in exploring new relationships and eliciting support from others, which leads to lower levels of social support following trauma.…”
Section: Introductionmentioning
confidence: 99%
“… 35 Protective factors against the development of PTSD in rape and sexual assault survivors include positive social support, 22 , 36 38 strong religious beliefs, 39 positive coping styles, 38 , 40 , 41 self-efficacy, 41 , 42 parental affection, 18 high internal locus of control, 41 and the finding of meaning in the experience. 37 , 39 Various studies have found a link between unresolved attachment (in adults), disorganized/insecure attachment (in infants), and increased likelihood of traumatic dissociation and PTSD symptom severity. 43 48 Insecure attachment is related to social withdrawal and a lack of confidence in exploring new relationships and eliciting support from others, which leads to lower levels of social support following trauma.…”
Section: Introductionmentioning
confidence: 99%
“…Dimensions of forgiveness include forgiveness of self, forgiveness of other, and forgiveness by God (Idler, 1999). Forgiveness of self and other may be experienced as a gift from God, as the grace that enables new life and possibilities in spite of violation (see Bowland et al, 2011). Some survivors also believe that in the aftermath of their traumatic experiences they have acted in ways that were unforgivable by God (promiscuity, substance abuse, neglecting or abusing their own children).…”
Section: Discussionmentioning
confidence: 99%
“…The hypotheses that the intervention would reduce depressive symptoms, anxiety, and somatic symptoms were supported at posttest and gains were maintained at 3-month follow up. More information about the original study, including the inclusion and exclusion criteria, and recruitment of participants is published elsewhere (see Bowland, Biswas, Kyriakakis, & Edmond, 2011;Bowland, Edmond, & Fallot, 2012;Bright & Bowland, 2008).…”
mentioning
confidence: 99%
“…Believers turn to their faith leaders and faith communities in challenging times. Various studies have shown how sexual violence survivors see their faith, faith leader and faith communities as having the ability to provide the support and solace that they need in order to deal with what happened to them [12,14,16,19,24]. Even if survivors are not receiving it, they believe that it can and should be provided.…”
Section: Introductionmentioning
confidence: 99%
“…Some religious beliefs and practices make it harder to cope and integrate traumatic experiences [ 12 , 13 ]. Furthermore, faith and faith institutions have been blamed for often perpetuating the unequal gender constructs, stigma and discrimination that contributes to the perpetration and normalisation of VAWG, as well as for ostracizing VAWG survivors, especially survivors of sexual violence [ 12 , 14 16 ]. With “patriarchy ha(ving) God on its side” [ 17 ], religion is recognised by some as being a key patriarchal structure within society.…”
Section: Introductionmentioning
confidence: 99%